School administrator's staff development activities manual - Hyman, Ronald T. (Englewood Cliffs, N.J. : Prentice-Hall, 1986)
Conducting a faculty meeting. Colored broken squares. The penny. The prisoner's dilemma. The supervision window. Sherlock. Winter crash survival. The spelling test.
Keywords: Education; Teachers; United States; Teachers -- In-service training -- United States -- Handbooks, manuals, etc; School supervision -- United States -- Handbooks, manuals, etc